2022
DOI: 10.1021/acsami.2c03014
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Foam 3D Printing of Microcellular Structures Using Material Extrusion Additive Manufacturing

Abstract: A facile manufacturing method to enable the in situ foam 3D printing of thermoplastic materials is reported. An expandable feedstock filament was first made by incorporation of thermally expandable microspheres (TEMs) in the filament during the extrusion process. The material formulation and extrusion process were designed such that TEM expansion was suppressed during filament fabrication. Polylactic acid (PLA) was used as a model material, and filaments containing 2.0 wt % triethyl citrate and 0.0–5.0 wt % TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 58 publications
(85 reference statements)
0
19
0
Order By: Relevance
“…The study performed by Kalia et al provides a good example of the significance of the FPW. 19 In their work, the authors attempted to fabricate 3D-printed foams using polylactic acid (PLA) as a matrix and thermally expandable microspheres (TEMs) as chemical blowing agents (CBAs). The overall workflow involved a two-step process, namely, (1) precompounding the PLA matrix and the TEM particles to create a filament and (2) feeding the resultant filament to the printer for foaming.…”
Section: Introductionmentioning
confidence: 99%
“…The study performed by Kalia et al provides a good example of the significance of the FPW. 19 In their work, the authors attempted to fabricate 3D-printed foams using polylactic acid (PLA) as a matrix and thermally expandable microspheres (TEMs) as chemical blowing agents (CBAs). The overall workflow involved a two-step process, namely, (1) precompounding the PLA matrix and the TEM particles to create a filament and (2) feeding the resultant filament to the printer for foaming.…”
Section: Introductionmentioning
confidence: 99%
“…This agreed well with the results from Evans et al [ 49 ], who found a twentyfold decrease in the viscosity of melts due to the introduction of superheated water into the melt system. The effect of nozzle temperature on the foam quality was studied by injecting equal amounts of CO 2 and water into the foam extruder, as it was identified as one of the most influential extruder settings for the foam quality due to cell nucleation taking place there [ 16 , 42 , 45 , 94 , 95 , 96 , 97 ]. This was studied for all processable blends; i.e., blends E3_PEG200_14 and E3_PEG200_20.…”
Section: Resultsmentioning
confidence: 99%
“…Despite in the early stages of study and not yet fully established, this foam 3D printing technique appears to be the most successful way to produce foamed printed structures (Nofar et al, 2022). There are now two proven techniques for in-situ foam 3D printing, with the key distinction being whether a single-phase polymer or a gaseous solution is reached before cell nucleation and growth (Kalia et al, 2022). Unexpanded filaments containing blowing agents, either physical or chemical blowing agents, are prepared in the first technique.…”
Section: In-situ Foam 3d Printingmentioning
confidence: 99%
“…As shown in Figure 12, PLA was employed as the feedstock material along with a polyethylene carrier, two weight percent triethyl citrate (TEC) plasticizer, and zero to five weight percent acrylonitrile-based TEM (Kalia et al, 2022). An improved extrusion procedure was used to create the unexpanded filaments, and then a commercially available printer was used to 3D print foam in place (Kalia et al, 2022). The degree of foam densities and TEM content was connected with the microstructure, cellular morphology, density, thermal and mechanical properties of the printed foams.…”
Section: In-situ Foam 3d Printingmentioning
confidence: 99%